INFLUENCE OF MULTICOMPONENT MIXES ON THE BASIS OF POLYETILENGLIKOL ON THE MAINTENANCE OF MICROELEMENTS AND AMINOACIDS IN BODIES AND FABRICS OF EXPERIMENTAL ANIMALS - Sirenko, E.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Ability of an organic mix on the basis of PEG is established to break mineral and albuminous exchanges in an organism of white rats. Dynamics of fund of microelements confirmed reduction of their maintenance in fabrics and the accelerated deducing from an organism. Infringements of an albuminous exchange were characterized by prevalence destroing processes above anabolic.